Does Equity Ownership Matter for Corporate Social Responsibility? A Literature Review of Theories and Recent Empirical Findings - Faller, Christian M. (Journal of business ethics, 2018)
Based on the concept of shareholder primacy, many scholars have argued that it is more important for businesses to earn profits for their shareholders than to provide benefits to society at large. Corporate social responsibility (CSR) is often regarded as an investment that comes at the expense of shareholders. In contrast, research analyzing the connections between the equity ownership structure of a company and its level of CSR engagement suggests that CSR offers benefits to shareholders that go beyond direct financial returns from investments. This study provides a comprehensive review and systematic assessment of theoretical considerations and approaches regarding different forms of equity ownership and their relationships to CSR, and it discusses the relevant benefits and motivations of shareholders. The perceived value of these CSR benefits varies among different types of shareholders, as they assign unequal values to short-term financial or to rather long-term CSR benefits. Based on a literature sample of 146 publications, this review demonstrates central problems inherent in previous analyses. Given the ambiguous and partially contradictory findings of prior research, this study identifies potential moderating influences that help clarify empirical evidence. A contingency approach is suggested in future research, as this can help resolve the problem of contradictory empirical findings and theoretical arguments.